Effect of autolyzed-shiitake (Lentinus edodes) on blood pressure and serum fat levels in spontaneously hypertensive rats - "Watanabe, T. (Himeji Inst. of Technology, Hyogo (Japan)); Yamada, T; Ishi, S; Mazumder, T.K; Nagai, S; Tsuji, K. (Nihon Shokuhin Kagaku Kōgaku kaishi, 2002)
"The effect of shiitake (Lentinus edodes, LE) and autolyzed- (fermented-) shiitake (Autolyzed-LE) on blood pressure and serum fat levels of spontaneously hypertensive rats (SHR) were studied. Powdered LE or Autolyzed-LE was fed to SHR at the levels of 2% in a 1% NaCl (control) diet for 21 days. The blood pressure was measured by tail cuff. The animals of the Autolyzed-LE group showed significantly lower blood pressure compared to the control or LE group. The serum levels of total cholesterol (TC), triglyceride and phospholipid of the groups fed with LE and Autolyzed-LE were lower than those of the control group, and atherogenic index [(TC-HDL-C)/HDL-C] improved significantly in 21 days. It was suggested that the serum TC decline is the action of eritadenine that is contained in the shiitake. An inhibitory activity of the angiotensin I-converting enzyme (ACE) was compared between of LE and Autolyzed-LE. The ICsub50 of LE and Autolyzed-LE for ACE were 2500 and 490microg/ml, respectively. Autolyzed-LE showed higher inhibitory activity than LE against the ACE. These phenomena suggested that the hypotensive action of Autolyzed-LE was due to concomitant ACE inhibitory activities of peptides and g-aminobutyric acid contained in higher amounts during the autolysis of LE."